Menavigasi Eksploitasi: Keamanan Manusia dalam Rantai Pasok Budi Daya Udang di Asia Tenggara - Dippo Alam Satrio; Siti Aliyuna Pratisti (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2025)
This study examines labor exploitation in shrimp farming supply chains in Southeast Asia. This study attempts to address this phenomenon by using human security theory to analyze global value chains. Southeast Asia has developed into one of the major shrimp producing regions and exports its shrimp to various developed countries, especially the European Union and the United States. This research uses qualitative methods through the study of secondary data, such as research reports, journal articles, and news. The findings of this research show how workers in the production stage experience economic, food, environmental, health and personal vulnerabilities and threats in Vietnam and Thailand. This is exacerbated by the GVC architecture that pressures developing countries to suppress their workers so that they can take a larger profit margin. This study finds that shrimp GVCs have created a systematic and interconnected system of multidimensional exploitation by targeting workers at the production level for corporate profits in the global market.